2017
DOI: 10.1016/j.chest.2017.03.061
|View full text |Cite
|
Sign up to set email alerts
|

A Multicenter, Randomized Trial of Ramped Position vs Sniffing Position During Endotracheal Intubation of Critically Ill Adults

Abstract: ClinicalTrials.gov; No.: NCT02497729; URL: www.clinicaltrials.gov.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
103
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(110 citation statements)
references
References 38 publications
4
103
0
3
Order By: Relevance
“…One randomized controlled trial of ramped versus sniffing head position during urgent intubations in the ICU found that ramping worsened the Cormack-Lehane grade view of the airway, while a similar study in an operating room population showed significantly better laryngeal views when patients were ramped. 20,21 Despite these mixed data, more than one-quarter of all patients in our study were placed in a ramped position. This parallels the percentage of patients listed as being either obese or morbidly obese.…”
Section: Discussionmentioning
confidence: 83%
“…One randomized controlled trial of ramped versus sniffing head position during urgent intubations in the ICU found that ramping worsened the Cormack-Lehane grade view of the airway, while a similar study in an operating room population showed significantly better laryngeal views when patients were ramped. 20,21 Despite these mixed data, more than one-quarter of all patients in our study were placed in a ramped position. This parallels the percentage of patients listed as being either obese or morbidly obese.…”
Section: Discussionmentioning
confidence: 83%
“…We appreciate the interest demonstrated by Dr Abdulmahdi et al in our recent multicenter randomized trial comparing ramped position to sniffing position during endotracheal intubation of critically ill adults. 1 Our trial found no difference in lowest oxygen saturation but a worse glottic view and an increased number of laryngoscopy attempts with a ramped position. Abdulmahdi et al highlight two important considerations: (1) the BMI of the patients and (2) their precise position during intubation.…”
Section: Responsementioning
confidence: 46%
“…1 Our trial found no difference in lowest oxygen saturation but a worse glottic view and an increased number of laryngoscopy attempts with a ramped position. Abdulmahdi et al highlight two important considerations: (1) the BMI of the patients and (2) their precise position during intubation.…”
Section: Responsementioning
confidence: 46%
“…Multiple studies on patients in the operating room have demonstrated that the head‐up position results in improved preoxygenation and increases the safe apnea time . Interestingly, a recent randomized controlled trial in critically ill patients in the ICU found that preoxygenation in the head‐up position resulted in no improvement in oxygenation compared to the supine position . The majority of the patients in this trial, however, had respiratory failure, many with shunt physiology, and this many have limited the benefits of upright preoxygenation.…”
mentioning
confidence: 82%